Impact of different concentrations of biogas slurry as a fertilizer substitute on the structure and gene distribution of microbial communities in oilseed rape soil - Yang, Xue; Zhang, Kai; Chen, YaYing; Zheng, Cancai; Lei, Chunlong; Song, Xiaoqin; Wen, Bin; Yuan, Xin; Liu, Hanyang; Zhu, Jiawen (Frontiers in Veterinary Science, 2025)
Application of biogas slurry (BS) in paddy fields offers a sustainable approach to reducing environmental risks while efficiently utilizing nutrients from biogas residues. However, BS may harbor animal gut microorganisms and associated antibiotic resistance genes (ARGs) arising from antibiotic use during livestock breeding, potentially facilitating the spread of resistance genes in soil ecosystems. In this two-year field study, we investigated the effects of replacing chemical fertilizers with different proportions of BS on the microbial communities in oilseed rape soils. Soil bacterial community diversity and composition were systematically evaluated using Illumina MiSeq high throughput sequencing, focusing on interrelationships and changes at the genetic level. The predominant bacterial phyla identified were Proteobacteria, Actinobacteria, and Bacteroidetes, with no significant differences observed at the phylum or species level across treatment groups. Overall microbial diversity and community structure remained largely stable. Dimensionality reduction analysis further revealed only minor variations in the abundance of ARGs, mobile genetic elements (MGEs), and metal resistance genes (MRGs) among treatments. These findings suggest that, in the short term, substituting chemical fertilizers with BS has minimal effects on soil microbial community structure and resistance gene dynamics. This study highlights the potential of BS as a viable alternative to chemical fertilizers, contributing to reduced environmental risks in agriculture. Future research should investigate the long-term ecological safety of BS under different soil types and management practices to comprehensively evaluate its sustainability in agricultural systems.